2020
DOI: 10.1101/2020.05.05.078642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple sclerosis iPSC-derived oligodendroglia conserve their intrinsic properties to functionally interact with axons and glia in vivo

Abstract: One Sentence Summary: Multiple Sclerosis oligodendroglia, regardless of major immune manipulators, are intrinsically capable of myelination and making functional axo-glia and glia-glia connections after engraftment in the murine CNS, reinforcing the view that the MS oligodendrocyte differentiation block is not due to major intrinsic oligodendroglial deficits but most likely to environmental conditions. 2 Abstract: The remyelination failure in multiple sclerosis (MS) is associated with a migration/differentiati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Thus, mouse and human skin‐derived remyelinating oligodendrocytes are capable of being integrated into the panglial network by establishing proper molecular connections with other glial cells to ensure their functionality. A recent dye‐coupling study of human iPSC‐derived oligodendrocytes grafted in the corpus callosum of newborn shiverer mice showed that the cells were capable of forming functional GJs with neighbor murine or human glial cells, indicating that exogenous cells could not only myelinate host axons, but also functionally integrate into the host pan‐glial network (Mozafari et al, 2020). Although not tested here, it is assumed that exogenous cells also proceed to functional integration into the host pan‐glial network during repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, mouse and human skin‐derived remyelinating oligodendrocytes are capable of being integrated into the panglial network by establishing proper molecular connections with other glial cells to ensure their functionality. A recent dye‐coupling study of human iPSC‐derived oligodendrocytes grafted in the corpus callosum of newborn shiverer mice showed that the cells were capable of forming functional GJs with neighbor murine or human glial cells, indicating that exogenous cells could not only myelinate host axons, but also functionally integrate into the host pan‐glial network (Mozafari et al, 2020). Although not tested here, it is assumed that exogenous cells also proceed to functional integration into the host pan‐glial network during repair.…”
Section: Discussionmentioning
confidence: 99%
“…We reported previously that following lysolecithin (LPC)‐induced adult demyelination, grafted iPSC‐NPCs/OPCs timely differentiate into oligodendrocytes (but also ~20% to astrocytes), and extensively remyelinate the lesion 6 weeks (rodent cells) or 12 weeks (human cells) after engraftment (Ehrlich et al, 2017; Mozafari et al, 2015; Mozafari et al, 2020). However, the timing and dynamics of loss and gain of Cx47 expression during demyelination and remyelination, and the potential interaction of the iPSC‐derived oligodendrocytes (through the connexins) with astrocytes during this successful remyelination has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Several promising ongoing research strategies for drug discovery of pharmacological compounds target OPC differentiation with the ultimate goal to find new treatments for progressive MS. Although, it is worth noting that human oligodendrocytes, derived from IPSCs of MS patients, have normal myelination properties and interact with axons when grafted in the shiverer:rag2 mouse brain [ 87 ], suggesting that the oligodendrocyte differentiation block is not related to an intrinsic defect of this cell type.…”
Section: Toward Remyelination and Repair In Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Newborns are one of the most at-risk groups for developing demyelinating diseases [ 1 ], characterized by loss of or damage to the central nervous system's oligodendrocytes (OLs), the primary myelin sheath-forming cells in the brain and spinal cord. Recovery from this disease requires myelin replacement through normal proliferation and differentiation of OLs [ 2 ]. Over the past few decades, a series of studies have been conducted on treatment of demyelinating diseases with cell transplantation.…”
Section: Introductionmentioning
confidence: 99%